Jupiter's auroral-related stratospheric heating and chemistry I: Analysis of Voyager-IRIS and Cassini-CIRS spectra - Sinclair, J; Orton, G; Greathouse, T; Fletcher, L; Moses, J; Hue, V; Irwin, P (Elsevier, 2017)
Auroral processes are evident in Jupiter's polar atmosphere over a large range in wavelength (X-ray to radio). In particular, previous observations in the mid-infrared (5-15 μm) have shown enhanced emission from CH4, C2H2 and C2H4 and further stratospheric hydrocarbon species in spatial regions coincident with auroral processes observed at other wavelengths. These regions, described as auroral-related hotspots, observed at approximately 160°W to 200°W (System III) at high-northern latitudes and 330°W to 80°W at high-southern latitudes, indicate that auroral processes modify the thermal structure and composition of the neutral atmosphere. However, previous studies have struggled to differentiate whether the aforementioned enhanced emission is a result of either temperature changes and/or changes in the concentration of the emitting species. We attempt to address this degeneracy in this work by performing a retrieval analysis of Voyager 1-IRIS spectra (acquired in 1979) and Cassini-CIRS spectra (acquired in 2000/2001) of Jupiter. Retrievals of the vertical temperature profile in Cassini-CIRS spectra covering the auroral-related hotspots indicate the presence of two discrete vertical regions of heating at the 1-mbar level and at pressures of 10-μbar and lower. For example, in Cassini-CIRS 2.5 cm-1 'MIRMAP' spectra at 70°N (planetographic) 180°W (centred on the auroral oval), we find temperatures at the 1-mbar level and 10-μbar levels are enhanced by 15.3 ± 5.2 K and 29.6 ± 15.0 K respectively, in comparison to results at 70°N, 60°W in the same dataset. High temperatures at 10 μbar and lower pressures were considered indicative of joule heating, ion and/or electron precipitation, ion-drag and energy released form exothermic ion-chemistry. However, we conclude that the heating at the 1-mbar level is the result of either a layer of aurorally-produced haze particles, which are heated by incident sunlight and/or adiabatic heating by downwelling within the auroral hot-spot region. The former mechanism would be consistent with the vertical profiles of polycyclic aromatic hydrocarbons (PAHs) and haze particles predicted in auroral-chemistry models (Wong et al., 2000; 2003). Retrievals of C2H2 and C2H6 were also performed and indicate C2H2 is enriched but C2H6 is depleted in auroral regions relative to quiescent regions. For example, using CIRS δν ˜= 2.5 cm-1 spectra, we determined that C2H2 at 0.98 mbar increases by 175.3 ± 89.3 ppbv while C2H6 at 4.7 mbar decreases by 0.86 ± 0.59 ppmv in comparing results at 70°N, 180°W and 70°N, 60°W. These results represent a mean of values retrieved from different initial assumptions and thus we believe they are robust. We believe these contrasts in C2H2 and C2H6 between auroral and quiescent regions can be explained by a coupling of auroral-driven chemistry and horizontal advection. Ion-neutral and electron recombination chemistry in the auroral region enriches all C2 hydrocarbons but in particular, the unsaturated C2H2 and C2H4 hydrocarbons. Once advected outside of the auroral region, the unsaturated C2 hydrocarbons are converted into C2H6 by neutral photochemistry thereby enriching C2H6 in quiescent regions, which gives the impression it is depleted inside the auroral region.